Training future educators to develop ecological knowledge of preschool and school children - Ivanchuk , Sabina; Moshura , Valeriia; Zelenin, Vsevolod (Revista Eduweb, 2023)
In the article, the basic principles of training future educators and teachers in the field of environmental education are discussed. Such a process requires mastering a set of innovative pedagogical knowledge on ecology to be aware of them in the future and integrate such knowledge into the profession of a teacher. This determined the relevance of the topic of this study. The article aims to determine the results of the effectiveness of the introduction of disciplines that increase the level of environmental knowledge and introduce innovative pedagogical methods in this area. It is equally important to determine the assessment of the usefulness of introducing new disciplines on methods of teaching environmental knowledge among students (attitude to innovations, anxious use of innovations, external barriers to the integration of innovations into pedagogical practice, readiness to use innovative pedagogical knowledge). A comprehensive approach to methodology was used in the study. The main method in the work is the method of pedagogical experiment. Moreover, descriptive, statistical, and theoretical methods are also applied. The methods of questionnaires and observation were employed to diagnose the effectiveness of innovative research, according to preschool teachers. The main hypothesis is the assumption that innovative environmental knowledge courses and self-education activities contribute to the competence and quality of teacher training significantly and provide for their integration into the work of school and preschool education. The result of this study is evidence that teacher training programs and new pedagogical methods related to innovations in ecological education affect the ability to operate with new methods and modern knowledge in future professional practice. A further prospect is the development and implementation of effective methods for introducing innovative pedagogical knowledge into the training of teachers in the field of preschool and school education.